The MANAJEMEN PEMBELAJARAN KITAB KUNING DI PONDOK PESANTREN SA’ADATUDDAREIN KELURAHAN TAHTUL YAMAN PELAYANGAN KOTA JAMBI - Mursid, Ahmad; Firdaus, Ali (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the management of kitab kuning learning at the Sa’adatuddarein Islamic Boarding School, Tahtul Yaman Village, Pelayangan, Jambi City. The focus of this research includes three main aspects of learning management, namely planning, implementation, and evaluation of kitab kuning learning. This research employed a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation involving the pesantren leader, teachers (ustadz), and students. Data analysis was carried out through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results show that the management of kitab kuning learning at the Sa’adatuddarein Islamic Boarding School is implemented through three main stages: planning, implementation, and evaluation. Learning planning is conducted through deliberation between the pesantren leader and teachers to determine learning materials, teaching assignments, and schedules. The learning process uses traditional pesantren methods such as bandongan, sorogan, question-and-answer sessions, and discussions. Evaluation is conducted through oral tests, written examinations, and direct observation of students’ ability to read and understand classical Islamic texts.